Peningkatan Kompetensi Siswa SMK dalam Menghadapi Ancaman Keamanan Siber - Nugroho, Agung; Widiyatmoko, Arif Tri; Siswandi, Arif; Susilo, Arief; Suwarno, Agus (Cahaya Pengabdian, 2025)
This community service aims to improve the competence of vocational school students in the field of cyber security through training activities and the effective use of learning technology. Vocational school students as prospective skilled workers need to be equipped with basic cybersecurity competencies to protect personal data and understand cyber risks. The method of implementing activities includes coordination with the school, module development, and intensive training using lecture, discussion, practicum, and demonstration methods. In addition, this activity utilizes information technology such as digital simulations for phishing and malware threats, as well as password strength testing tools. The results of the service showed that the activities carried out ran smoothly and had a positive impact in improving students' understanding and competence of cyber security threats. This service is expected to produce graduates who have critical thinking, creative, and problem-solving skills who are ready to enter the world of work